THE PERCEPTION OF SMALLHOLDER FARMERS TOWARD MICRO-INSURANCE AS A RISK COPING STRATEGY IN ZIMBABWE - Chrispen Maireva (Agricultural Socio-Economics Journal, 2023)
Microinsurance is an important risk mitigation strategy in smallholder farmers’ agricultural enterprises that are faced with intensifying climate change and unpredictability. This study analysed the perceptions of smallholder tobacco farmers in Zimbabwe’s tobacco-growing regions of the Mashonaland Provinces towards microinsurance as a risk coping strategy given the risks of hailstorms, droughts, and long-dry spells in the rainy season. A qualitative phenomenological study was conducted with 13 purposively selected small-scale tobacco farmers. The study employed unstructured interviews to collect data from the participants. The findings of the study suggest that smallholder farmers have a positive perception of microinsurance, against the general view that they have a negative attitude. The study found that other risks with which smallholder farmers are faced and their immediate risk response, tolerance and disposition may have a distorting effect on the smallholder farmers’ perceptions and attitude towards microinsurance. It was further found that the perception of the smallholder farmers was also influenced by whether the farmers had other sources of income, whether they previously had experienced crop losses due to weather-induced risks and the general level of education of the smallholder farmer. It was also found that most of the micro-insurance services offered were mainly supply-side driven rather than demand-side driven and as a result, most of the products were not farmer-centric. New product development, farmer-centric insurance service offerings and general farmer sensitisation on the need for microinsurance were recommended.